Photocrosslinking of Silk Fibroin Using Riboflavin for Ocular Prostheses. Issue 12 (29th January 2016) - Applegate, Matthew B.; Partlow, Benjamin P.; Coburn, Jeannine; Marelli, Benedetto; Pirie, Christopher; Pineda, Roberto; Kaplan, David L.; Omenetto, Fiorenzo G.
Abstract : A novel method to photocrosslink silk fibroin protein is reported, using riboflavin (vitamin B2) as a photoinitiator and the mechanism of crosslinking is determined. Exposure of riboflavin‐doped liquid silk solution to light results in the formation of a transparent, elastic hydrogel. Several applications for this new material are investigated including corneal reshaping to restore visual acuity and photolithography.